Identification of intestinal nematode eggs in cabbage (brassica oleracea) at seafood sellers - Nuril Sofiantin (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Cabbage is one of the staple food companions that are rich in nutrients. In vegetables contained protein, vitamins, and minerals. As a vegetable, cabbage contains many vitamins and minerals that are needed by the human body. Helminthic diseases are currently still a health problem in the tropics, including Indonesia. The intestinal nematodes of the soil transmitted helminth group are ascaris lumbricoides, trichuris trichiura, strongyloides stercoralis, and hookworm. the purpose of this study was to determine the presence of intestinal nematode eggs in cabbage vegetables at seafood food stalls in makassar city. This type of research is a laboratory test using purposive sampling techniques with a total of 12 seafood stalls. Examination of intestinal nematode eggs using the flotation method. The results of this study from 12 cabbage samples examined found no intestinal nematode eggs. It was concluded that negative results or no intestinal nematode eggs were found (ascaris lumbricoides, trichuris trichiura, necator americanus, and duodenale ancylostoma).